Domestic violence risk assessment: tools for effective prediction management - Hilton, N. Zoe (American Psychological Association, 2021)
"The second edition of this authoritative text helps professionals charged with curbing domestic violence to assess and manage offenders and their risk of recidivism. With thoroughly updated guidelines and scoring manuals based on user experiences and international research, this book presents a comprehensive risk assessment system comprised of the Ontario Domestic Assault Risk Assessment (ODARA) and the Domestic Violence Risk Appraisal Guide (DVRAG). It demonstrates how to score, interpret, and communicate the results of these evaluations, and how to incorporate their results into broader discussions of public policy. The detailed guidelines in this manual are accessible to a wide interdisciplinary audience, including psychologists, victim service and child protection workers, lawyers, police, and threat analysts. Also new to this edition are coverage of female offenders, alongside male offenders, and further guidance for assisting victims of domestic violence, making this a crucial resource for ensuring victim safety, treating offenders, and informing criminal justice procedures through empirically informed research and practice"--